Research Progress in Antineoplastic, Antibacterial, and Anti-inflammatory Activities of Seven-membered Heterocyclic Derivatives - Li, Bin; Chen, Chen; Jia, Jingjing; He, Ling (Current Medicinal Chemistry, 2022)
Seven-membered heterocyclic compounds are important drug scaffolds because of their unique chemical structures. They widely exist in natural products and show a variety of biological activities. They have been used commonly in central nervous system drugs in the past 30 years. In the past decade, many studies have been conducted on their activities, including antitumor, antibacterial, etc. Herein, we summarize the research advances in different kinds of seven-membered heterocyclic compounds containing nitrogen, oxygen, and sulfur heteroatoms with antitumor, antisepsis, and anti-inflammation activities in the past ten years, which are expected to be beneficial to the development and design of novel drugs for the corresponding indications.
Keywords: heterocyclic compounds